Chemical Investigation of Danthania cachemyriana (Jaub and Spach) of Kumaun Hills at Different Stages of Growth - Pant, C.S.; Dhami, K.S. (Asian Journal of Chemistry, 2016)
Danthania cachemyriana (Jaub and Spach), a perennial fodder grass of high altitude was investigated for its chemical constituents at different stages of growth from July to October 2000-2001. This fodder grass was found to contain sufficiently high level of all the chemical constituents and hence assessed as a good quality fodder.